Heat Transfer of Fluid Flow by Conduction and Convection in Inclined Cavities - Hamsa Saleem (Al-Rafidain Journal of Computer Sciences and Mathematics)
This research dealt with a numerical simulation of the issue of heat transfer by conduction and convection in two dimensions resulting from the flow of a fluid in horizontal and inclined channels. The channel walls are long H and wide L and consist of a porous material. Ode45 techniques were used to represent the governing equations (volume, momentum, and energy) after converting them to non-dimensional formulas using some appropriate transformations. The results showed the effect of the Reynolds number, Prandtl number, Rayleigh number, Hartmann number, Darcy number, in addition to the angle of inclination, on the problem, as shown in the drawings and illustrations